KEGIATAN COMMUNITY OUTREACH PADA BIOKONSERVASI DI BIDANG SAINS - Muhammad Nazri Janra (LPPM Universitas Andalas, 2018)
Community Outreach (CO) activity is an object taught in the Bioconservation Lab (BIO 4012), which since three years ago added as part of lab materials. This lab is mandatory for students at fifth semester in Biology Department, Faculty of Mathematics and Natural Sciences, Andalas University. This paper descriptively analyzes the conducts of CO as it may be considerable as part of the community services independently performed on the department or study program level. The analysis focused on the 2017’s CO activities, by comparing the proposals and reports given by the students who conducted the CO and then complemented with data gained through Focus Group Discussion on each student group. The 2017 CO activities brought up conservation and applied biology as their main topics, and targeted groups in society as well as students in elementary and middle schools. Feedbacks given by the targeted audiences complimented the CO activities as it complements the school curriculum by adding conservation and applicative biology aspects. Moreover, these activities retain potential to generally improve people awareness on the protection of environment. This study recommends the continuity of CO activity, by paying attention on some weaknesses and technical difficulties recorded on 2017 CO activities and improving it in the future.